Hubungan Usia, Indeks Massa Tubuh (IMT), Aktivitas Fisik, Riwayat Merokok terhadap Tekanan Darah pada Lansia - Kusumaningtyas, Mei; Handari, Herdianty Kusuma; Darmawan, Iwan Dwi (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Elderly individuals are an age group vulnerable to various health problems, one of which is hypertension. Hypertension in the elderly can be influenced by several factors, including age, Body Mass Index (BMI), physical activity level, and smoking history. Objectives: This study aimed to determine the relationship between these factors and blood pressure in the elderly. Methods: This research employed a cross-sectional design with a quantitative approach. The study subjects were elderly aged ≥60 years living in the area of Posyandu Lansia Brotoseno, Indronatan Village, Kartasura Subdistrict, Sukoharjo Regency. Data were collected through interviews, BMI measurement, and blood pressure examination, then analyzed using Spearman and Kendall’s Tau correlation tests. Results: The findings showed a significant positive correlation between age and blood pressure (p=0.00; r=0.630), no significant correlation between BMI and blood pressure (p=0.263; r=-0.161), a significant negative correlation between physical activity and blood pressure (p=0.00; r=-0.572), and no significant correlation between smoking history and blood pressure (p=0.196; r=0.169). Conclusion: The study concludes that age and physical activity are significantly associated with blood pressure in the elderly, while BMI and smoking history are not significantly related. Keywords: Age, BMI, Physical activity, Smoking history, Blood pressure, Elderly